2019
DOI: 10.1017/s1742170519000140
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and sustainability of agroforestry in temperate industrialized agriculture: preliminary insights from California

Abstract: Intensive use of external inputs in specialized industrial farming systems has created significant socio-ecological externalities, including water and air pollution from nutrients and pesticides, soil erosion and depletion of carbon stocks, biodiversity loss and rising production costs. Ecological intensification is a strategy for reducing reliance on inputs by intentionally designing agroecosystems to harness biological processes and ecological relationships for the sustainable functioning of the system. Inco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 55 publications
1
4
0
Order By: Relevance
“…In line with our results (Fig. 5.4), the lack of appropriately customised equipment has been put forward as a major challenge to scaling agroforestry in places as diverse as California in the USA (Brodt et al, 2019), Kenya (Nyberg et al, 2020) India (Upendranadh and Subbaiah, 2016) and Northern Europe (Graves et al, 2009).…”
Section: Challenges For Scaling Complex Agroforestrysupporting
confidence: 87%
See 2 more Smart Citations
“…In line with our results (Fig. 5.4), the lack of appropriately customised equipment has been put forward as a major challenge to scaling agroforestry in places as diverse as California in the USA (Brodt et al, 2019), Kenya (Nyberg et al, 2020) India (Upendranadh and Subbaiah, 2016) and Northern Europe (Graves et al, 2009).…”
Section: Challenges For Scaling Complex Agroforestrysupporting
confidence: 87%
“…It has been shown that for some agroforestry farmers keeping labour demand moderate is even more important than maximising productivity (Fujisawa et al, 2020;Scudder et al, 2022;Tilden et al, 2023) and in the future, labour availability is projected to be a major constraint for farmers (Ryan, 2023). It is often postulated that adopting more complex agroforestry systems increases labour demand (Brodt et al, 2019;Esche et al, 2022;Scudder et al, 2022;Smith et al, 2022), but labour inputs required to perform specific activities, such as weeding, might also decrease (Armengot et al, 2016). It is therefore relevant to assess the impact of agroforestry complexity on total labour demand, and also on specific labour activities.…”
Section: Knowledge Gapsmentioning
confidence: 99%
See 1 more Smart Citation
“…Simultaneously, following the rehabilitation of degraded and desertified cropland, local governments promote adjustments to agricultural structures to reduce excessive land utilization. This may involve guiding farmers to diversify into other industries or altering crop planting patterns, such as promoting drought-resistant crops, crop rotation and fallow practices, and developing multi-story agroforestry [59]. These measures not only secure income for the impoverished population but also reduce the overexploitation of cropland, safeguarding the ecological environment from degradation and mitigating instances of unregulated cropland expansion due to livelihood constraints.…”
Section: Theoretical Mechanismsmentioning
confidence: 99%
“…Cover crops offer flexible management options for diversifying agroecosystems and increasing the ecological function of orchard floors (Brodt et al 2019). As one cultural management practice within a suite of integrated pest management practices, cover crops can provide a framework for understanding the seasonality and phenology of weed life cycles while also promoting grower acceptance for some level of orchard vegetation (Linares et al 2008;Ramos et al 2010).…”
Section: Introductionmentioning
confidence: 99%